Sin, Spirituality, and Primitivism: The Theologies of the American Social Gospel, 1885–1917 - Bowman, Matthew Burton (Religion and American culture, 2007)
This article seeks to draw attention to an often overlooked aspect of the social gospel. Rather than explaining social gospelers as theological liberals who took an interest in social problems, as many historians have done, this essay argues that they were possessed of a unique theology, one which welded evangelical ideas of conversion and experiential Christianity with liberal postmillennial hopes. Their devotion to combating social ills should be understood, therefore, not solely as a secular commitment to social justice or a nebulous allegiance to Christian charity but also as a theological obligation tied to evangelical conversion and a repudiation of social sin, a crime as offensive to God as murder or theft. The social gospelers modeled the ideal Christian society upon that of the biblical patriarchs, one in which no distinction between the secular and sacred existed and sanctification guided the Christian's actions in the economy as well as in personal morality. That society, that postmillennial Zion, would come again when all humanity experienced a spiritual conversion and were truly born again as Christians—a transformation not limited to individual salvation but which brought with it a new understanding of the nature of Christian life.